Mali : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2003)
This paper examines the Poverty Reduction Strategy Paper (PRSP) for Mali. The PRSP is an expression of the government's desire to engage in development activity that is more intense, more organized, more consensus-based, and more effective, and capable of bringing about lasting poverty reduction. Although redistribution activities and social protection systems are necessary in the short term to reduce the impact of poverty, it is above all a matter of integrating these activities into long-term strategies that will put the poor in a position to help further their own economic and social well-being.